Rapid demographic change and the allocation of public education resources: Evidence from East Germany - Gerhard Kempkes (Deutsche Bundesbank, 2010)
We analyse the adjustment of public education spending in response to rapidly decreasing student cohorts in East Germany where birth rates collapsed after German reunification. Previous results from the literature based on data from more stable demographic periods suggest that public resources are incompletely adjusted, and that large reductions in the student population would thus translate into major increases in spending per student. Our empirical analysis suggests, however, that resource adjustments in East Germany have been considerable, especially in the years when student cohorts actually decreased. Adjustments were less tight when student numbers began to stagnate. Although our results are restricted to public education, they may be interpreted as early evidence on fiscal adjustments during strong demographic change, which will play a growing role in the years to come.
Keywords: I22; J18; H72; 330; Subnational government spending; demographic change; public education; Öffentliche Bildungsausgaben; Anpassung; Fruchtbarkeit; Bevölkerungsentwicklung; Neue Bundesländer; Finanzpolitik; Alternde Bevölkerung; Deutschland